Predicting Smart Grid Stability Using Advanced Machine Learning Techniques - Chintala Deepak Srinivas; M Kavitha (Utilitas Mathematica, 2025)
An electric lattice incorporates transformers, era centers, communication joins, control stations, along with wholesalers, all of which together permit for the exchange of power from control stations to commercial and private customers . Customary electrical systems cannot predict quick shifts in electricity demanded by users and often lack adequate flexibility and robustness. This limitation has overwhelmingly driven onward the transition into modern smart grids—new electrical systems adequately designed for being self-healing, durable, and adaptive for constantly evolving client needs. Machine learning has emerged as an influential tool in the enhancement of grid stability via dealing with the challenges posed by dynamically shifting demands. This transformation decidedly minimizes the risk of breakdowns, ensuring a reliably more efficient grid system. In this analysis, advanced machine learning methods, inclusive of the CatBoost framework, were used in terms of grid stability prediction with a Kaggle-hosted public dataset. The experiments were conducted in a largely Python-based simulation environment. They leveraged thorough preprocessing, careful feature scaling, and refined predictive modelling techniques. The prior CatBoost-based model achieved a great accuracy of 98.96% during load stability prediction. This accurate forecasting of power demand notably reduces the likelihood of grid failure, improving the stability, reliability, as well as the robustness of the smart grid system.